“Holding so Much of the Mind of Ireland” and Writing Modernist Drama: Celebratory Thoughts on the 150th Anniversary of the Birth of John Millington Synge - Kurdi, Mária (Hungarian Journal of English and American Studies, 2021)
Celebratory Thoughts on the 150th Anniversary of the Birth of John Millington Synge